A comparative study of rock art in later Prehistoric Europe - Bradley, Richard 1946- (Cambridge University Press, 2020)
The Element summarises the state of knowledge about four styles of prehistoric rock art in Europe current between the late Mesolithic period and the Iron Age. They are the Levantine, Macroschematic and Schematic traditions in the Iberian Peninsula; the Atlantic style that extended between Portugal, Spain, Britain and Ireland; Alpine rock art; and the pecked and painted images found in Fennoscandia. They are interpreted in relation to the landscapes in which they were made. Their production is related to monument building, the decoration of portable objects, trade and long distance travel, burial rites, and warfare. A final discussion considers possible connections between these separate traditions and the changing subject matter of rock art in relation to wider developments in European prehistoric societies
Title from publisher's bibliographic system (viewed on 21 Sep 2020)
Keywords: Petroglyphs / Europe; Rock paintings / Europe; Graffiti / Europe; Landscape assessment / Europe; Felsbild; Europe / Antiquities; Europa